Australian trachoma surveillance annual report, 2011 - Cowling, C.; Liu, B.; Ward, J.; Snelling, Thomas; Kaldor, J.; Wilson, D. (2013)
This work is copyright. Apart from any use as permitted under the Copyright Act 1968, no part may be reproduced by any process without prior written permission from the Commonwealth. Requests and inquiries concerning reproduction and rights should be addressed to the Commonwealth Copyright Administration, Attorney General's Department, Robert Garran Offices, National Circuit, Barton ACT 2600 or Australia remains the only developed country to have endemic trachoma in some regions. Endemic levels of trachoma in Australia are found predominantly in remote and very remote Aboriginal communities. Data are collected from Aboriginal communities designated at risk for endemic trachoma (defined as a prevalence of 5% or greater among children) in the Northern Territory, South Australia and Western Australia. This report presents data collected in 2011. The World Health Organization (WHO) grading criteria were used to diagnose cases of trachoma in Aboriginal children with jurisdictions focusing screening activities on the 5-9 year age group. The prevalence of trachoma within a community was used to guide appropriate treatment strategies as a public health response. Aboriginal adults aged 40 years or older were screened for trichiasis. Population screening coverage for trichiasis in 2011 was 9% with a prevalence of 2% in those adults screened. Trachoma screening coverage of the estimated populationof children aged 5-9 years in at-risk communities was 65%. Trachoma prevalence among children aged 5-9 years who were screened was 7%. Of the communities screened, 47% were found to have no cases of active trachoma and 40% were found to have endemic levels. Treatment was required in 80 at-risk communities screened. Treatment coverage of active cases and their contacts varied between jurisdictions, ranging from 53% to 98%. This report provides evidence of increasing coverage of trachoma screening and control activities. In the Northern Territory and Western Australia, there is also evidence of a decline in the prevalence of infection that may be attributable to an improvement in control activities. Despite these apparent advances, trachoma prevalence remains at endemic levels in many communities in remote Australia. Continued efforts are required to ensure that Australia remains on track to reach the goal of elimination by 2020 or sooner.